Khettaras in the Tafilalet oasis (Morocco): contribution to the promotion of tourism and sustainable development - Mohamed Beraaouz; Mohamed Abioui; Mohammed Hssaisoune; Jesús Martínez-Frías (Built Heritage, 2022)
Abstract The khettaras constitute a hydraulic system for mobilising water by gravity from the water table to the surface to irrigate fields in oases. This system, which has been fairly widespread in North Africa, in particular in Algeria (foggara) and Morocco (khettaras), was introduced several centuries ago in the oases of southeastern Morocco and has continued to operate despite various natural and anthropic constraints. Based on these ingenious and millennial hydraulic systems, successive civilisations living in these environments have been able to establish laws and regulations for the management and mobilisation of natural resources, especially water. Indeed, to get the most out of these systems, users have had to abide by rules (Al Orf/Azref) designed to protect, promote, and care for the systems to enhance their sustainability. These hydraulic systems have declined in recent years, notably due to extensive groundwater pumping, climate variability (severe droughts), and the local population’s disinterest for this type of development. Therefore, we have unfortunately witnessed the loss of a thousand-year-old local ancestral know-how that had been developed by different succeeding civilisations in the area. Recent initiatives (2008–2011) have been undertaken by the Moroccan government for the restoration and development of some abandoned khettaras in the Tafilalet Oasis so that they could be utilised in the development of an oasis-based cultural tourism and integrated in a tourist circuit known as Majhoul. This initiative, still in its infancy, has constituted an alternative and a fairly encouraging development for this national and world heritage.